Botanical Printing dari Tumbuhan Pteridophyta Tahura KGPAA Mangkunagoro I - Dewi Puspita Sari; Yessy Ratna Siwie; Alfian Primahesa; Harlita Harlita (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2022)
Botanical printing is a method of printing motifs from plant parts such as leaves, flowers, and bark onto natural fiber media, animal skin, ceramics, and wood. Botanical printing products generally use mordants (metals and minerals) and natural dyes from species of seed plants. Research on pteridophytes in Tahura KGPAA Mangkunagoro I has been conducted in 2019, but is still limited to identification and has not been utilized for art crafts. The purpose of this study is to create textile products with pteridophyte leaf motifs from the Tahura KGPAA Mangkunagoro I area. The type of research conducted is qualitative descriptive research. Sampling was done using purposive sampling techniques. The creation of botanical printing art crafts uses textile materials from plants such as rayon and canvas. The textile raw materials are processed using steaming techniques. The research results show that 20 species of pteridophytes from 9 different families (Polypodiaceae, Thelypteridaceae, Lycopodiaceae, Nephrolepidaceae, Dryopteridaceae, Pteridaceae, Hymenophyllaceae, Asplenidaceae, Athyriaceae) can be used as a source of natural motifs in the creation of botanical printing art crafts.